Discourse on Conditional Death Penalty through Probationary Period of Imprisonment Under the New Criminal Code in Perspective of Restorative Justice - Ariawan, Dwi (Faculty of Law, Universitas Lampung, 2024)
One of materials in New Criminal Cod states that the mandatory 10-year probation period for death row inmates in the latest Criminal Code (KUHP) is a solution taken to mediate between the ideas of the pros and cons of the death penalty The rules on the death penalty are regulated in Article 100 of the new Criminal Code. The article states that judges can impose death penalty with probation for 10 years by taking into account two things. After serving a 10-year probation period, death row inmates will be given an assessment. This becomes the basis for a recommendation whether the convicted person's sentence will remain or be changed to life imprisonment. if the death row convict is considered to be behaving well and changing, then the President will issue a Presidential Decree (Keppres) to change the convict's sentence to life imprisonment. The doctrinal approach is carried out by conducting a study of the principles, regulations and applicable laws and regulations relating to the legal issues to be discussed. Data collection used in this research includes this writing is done in 2 (two) ways, namely primary data and secondary data. The study's findings suggest that this provision could result in corruption from the convicted party to the head of the correctional facility, the Supreme Court, which makes recommendations to the President and the Attorney General's Office regarding the application of the death penalty. In addition, it presents a chance for diplomatic relations between other nations and Indonesia, as its citizens face the possibility of having their sentences reduced to life in prison, and other nations undoubtedly want their citizens to be free from the fear of such punishment.